Economic Essence Of Green Urbanization Policy And Its Role In Sustainable Development - Zaylobiddinov, Diyorbek (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
The article analyzes the economic essence of green urbanization policy and its role in sustainable development. The ecological, economic and social consequences of urbanization processes in the world and Uzbekistan are considered, and the importance of the concept of green urbanization is highlighted. It is shown that the structural elements of green urbanization - energy-efficient technologies, green areas, sustainable transport systems, waste recycling and "smart city" technologies - are effective tools for ensuring economic stability, social well-being and ecological balance. The prospects, practical projects and future prospects of green urbanization in the conditions of Uzbekistan are analyzed, and the strategic importance of creating sustainable cities is emphasized.